Identification of abnormal states of traffic computer networks based on the paradigm of multidimensional networks - Минаев, Ю. Н.; Гузий, Н. Н.; Филимонова, О. Ю. (Problems of Informatization and Management, 2010)
The questions of presentation of traffic to computer network by invariants a tensor 4-го rank, in turn traffic is consider as a flow of tensors 2-nd rank multivariate network are considered. The efficiency of using an offered approach for identifications of anomalous conditions a computer network is shown